Budaya Tradisional, Identitas Dan Media Baru: Representasi Pacu Jalur Pada Instagram @Kuantanesia - Fz, Yudhisti Indra; Salam, Noor Efni; Yozani, Ringgo Eldapi (CV. ITTC INDONESIA, 2026)
The Pacu Jalur tradition is a cultural heritage of the Kuantan Singingi community that faces significant challenges due to changing media consumption patterns and the dominance of global digital culture. This study aims to analyze how the Instagram account @kuantanesia contributes to the preservation of Pacu Jalur’s cultural identity through visual representation practices, cultural storytelling, and strategies for leveraging social media algorithms. This research employs a qualitative descriptive approach, including content observation, visual analysis, and digital interaction tracing related to the cultural activities of Pacu Jalur. The study adopts Regina Luttrell’s Circular Model of Social Media as the conceptual framework to map the digital communication practices used by @kuantanesia in conveying cultural messages.The findings reveal that @kuantanesia functions not only as a documentation platform but also as a cultural intermediary that reconstructs Pacu Jalur’s identity through visual aesthetics, localized storytelling, and the use of Instagram features such as photos, short videos, and Reels. Consistent cultural representation enhances the visibility of cultural content and strengthens the collective memory of the Pacu Jalur tradition among the public. Additional findings indicate that algorithmic strategies including posting frequency, hashtag usage, and visual narrative styles significantly contribute to increased reach and user engagement. This study concludes that social media serves as a space for cultural revitalization as well as an arena for identity negotiation amid the symbolic competition of global digital culture.